State defence education among the younger generation - Zahira, Inayah Junika; Putri, Mas Fierna Janvierna Lusie (Universitas Cokroaminoto Yogyakarta, 2024)
National defense education equips us with the knowledge and skills needed to uphold our duties as citizens in defending our country from internal and external dangers. The research method used in this research is the literature method with data collected from books, journals and other reading materials. The aim of this research is to explain the importance of national defense education for the younger generation as agents of change. Apart from that, the importance of national defense education is also outlined in a number of articles and poems which provide encouragement to those who uphold the country, are ready to defend honor and dignity, and are able to raise national pride. State defense education is a solution for national unity and unity. By cultivating a mindset of love for the country of the younger generation. This can also prevent radicalism. Radicalism can destroy the integrity of the Republic of Indonesia.